Phosphorus requirement for juvenile jundiá (Rhamdia quelen) on a semi-purified diet (Research, Society and Development, 2020)
The aim of the present study was to determine the total phosphorus requirement in the diet of jundiá fry (Rhamdia quelen) in a semi-purified diet. A quantitative experimental research was carried out, using dehydrated albumin as a protein source, with the supplementation of monobasic sodium phosphate at different levels: 0.04; 0.30; 0.47 and 0.70% of total phosphorus (P). 160 fish with an average weight of 1.20 ± 0.53g were used in an experimental or completely randomized design, with four treatments and four replications. The experiment lasted 33 days. To determine the phosphorus requirements for juveniles, body chemical composition, bone mineral composition and productive performance parameters were evaluated. The body chemical composition only the levels of protein did not present significant difference (p˃0.05). The levels of phosphorus, potassium and magnesium in the bones increased linearly, with increased levels of phosphorus in the diet. Based on weight gain and total length, the requirement for phosphorus for juveniles of jundiá (Rhamdia quelen) in a semipurified diet is between 0.53 - 0 5.8% of P-total.